Efficacy of Supplementing Ashwgandha Extract (Withania Somnifera) on Immunity and Serum Biochemistry in Broilers during Summer - Kumar, K. Prashanth; Reddy , V. Ravinder; Prakash, M. Gnana (International Journal of Livestock Research, 2018)
The objective of the present study was to determine the effects of different levels of Ashwagandha (Withania somnifera) extract (WSE) on immunity and serum biochemical parameters of broiler chicken reared during hot summer. The average minimum and maximum room temperatures recorded from 0-42 day were 36.8oC±0.25 – 39.7oC±0.25, respectively, with relative humidity ranging from 47 – 74%. Day old broiler chicks (n=160) were randomly allotted to 4 dietary groups with eight replicates of five birds each. The four dietary groups were Positive control (PC) with vit-E (70mg/kg) +Se (0.15mg/kg), Negative control (NC), WSE50 and WSE100 groups supplemented with WSE 50mg/kg and 100mg/kg, respectively. Serum cholesterol levels were significantly (P<0.05) reduced in WSE50 and WSE100 groups, while serum protein levels were unaffected (P>0.05) by supplementation of WSE. Humoral immune response in terms of NDV (Newcastle disease virus) titer and cell mediated immunity in terms of cutaneous basophilic hypersensitivity (CBH) were not significantly influenced by supplementation of WSE in broiler diets.